Virus-induced inhibition of cardiac pacemaker channel HCN4 triggers bradycardia in human-induced stem cell system - Peischard, Stefan; Möller, Melina; Disse, Paul; Ho, Huyen Tran; Verkerk, Arie O.; Strutz-Seebohm, Nathalie; Budde, Thomas; Meuth, Sven G.; Schweizer, Patrick Alexander; Morris, Silke; Mücher, Lena; Eisner, Verónica; et al. (Cellular and molecular life sciences, 2022)
The enterovirus Coxsackievirus B3 (CVB3) is known to be a major source for the development of cardiac dysfunctions like viral myocarditis (VMC) and dilatative cardiomyopathy (DCM), but also results in bradycardia and fatal cardiac arrest. Besides clinical reports on bradycardia and sudden cardiac death, very little is known about the influence of CVB3 on the activity of human cardiac pacemaker cells. Here, we address this issue using the first human induced pluripotent stem cell (hiPSC)-derived pacemaker-like cells, in which the expression of a transgenic non-infectious variant of CVB3 can be controlled dose- and time-dependently. We found that CVB3 drastically changed hyperpolarization-activated cyclic nucleotidegated channel 4 (HCN4) distribution and function in hiPSC-derived pacemaker-like tissue. In addition, using HCN4 cell expression systems, we found that HCN4 currents were decreased with altered voltage dependency of activation when CVB3 was expressed. Increased autophagosome formation and autophagosomal HCN4 insertion was observed in hiPSC-derived pacemaker-like cells under CVB3 expression as well. Individual effects of single, non-structural CVB3 proteins were analyzed and demonstrated that CVB3 proteins 2C and 3A had the most robust effect on HCN4 activity. Treatment of cells with the Rab7 inhibitor CID 106770 or the CVB3-3A inhibitor GW5074 led to the recovery of the cytoplasmatic HCN4 accumulation into a healthy appearing phenotype, indicating that malfunctioning Rab7-directed autophagosome transport is involved in the disturbed, cytoplasmatic HCN4 accumulation in CVB3-expressing human pacemaker-like cells. Summarizing, the enterovirus CVB3 inhibits human cardiac pacemaker function by reducing the pacemaker channel plasma membrane density, an effect that can be corrected by pharmacological intervention of endocytic vesicle trafficking.
Gesehen am 21.09.2022